2000
DOI: 10.1021/es001320l
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Sorption Isotherms of Polar and Apolar Compounds in a High-Organic Soil

Abstract: Sorption isotherms of 13 apolar liquids and solids and polar solids-six in unprecedented detail-are used to evaluate a polymer-based model for natural organic matter. While all isotherms are nonlinear, the "running" Freundlich exponent n varies markedly with concentration. The isotherms show linear-scale inflection consistent with the presence of flexible (deformable) porosity as predicted by the glassy polymer-based Extended Dual-Mode Model (EDMM). The EDMM assumes dissolution and hole-filling domains in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 45 publications
10
130
1
Order By: Relevance
“…As the isotherm temperature is increased, the size of the hysteresis loop is predicted to decrease until the glass transition temperature of the material is reached, at which point it becomes zero. The glass transition temperature of lignin in the presence of moisture is in the region of 60 to 90 C 61 and linear projections of the decrease in hysteresis loops reached zero in this temperature range for Sitka spruce.…”
Section: Effect Of Temperature On Isotherms and Heat Of Wettingmentioning
confidence: 94%
“…As the isotherm temperature is increased, the size of the hysteresis loop is predicted to decrease until the glass transition temperature of the material is reached, at which point it becomes zero. The glass transition temperature of lignin in the presence of moisture is in the region of 60 to 90 C 61 and linear projections of the decrease in hysteresis loops reached zero in this temperature range for Sitka spruce.…”
Section: Effect Of Temperature On Isotherms and Heat Of Wettingmentioning
confidence: 94%
“…The BC comprised carbonized and noncarbonized fractions, which demonstrated that BC was heterogeneous (Chen et al 2008;Cao et al 2009). The sorption for AT by BC had two principal types of sorption domains; one was a soft carbon domain analogous to rubbery polymers and characterized by a PEER-REVIEWED ARTICLE bioresources.com partition mechanism exhibiting a linear sorption behavior, and the other was a hard carbon domain analogous to glassy polymers and characterized by a pore-filling mechanism; its sorption behavior was nonlinear (Xia and Pignatello 2001). Sorption isotherms of AT in BC-added soil were linear/nonlinear (Fig.…”
Section: Sorption Isothermmentioning
confidence: 99%
“…Therefore, the adsorption of NOR on biochars have two principal types of sorption domains. One is a soft carbon domain similar to rubbery polymers, which is characterized by a partition mechanism to exhibit a linear; the other is a hard carbon domain analogous to glassy polymers, characterized by a pore-filling mechanism, which sorption isotherm is nonlinear (Xia and Pignatello 2001). Hence, for BC450 and BC550, partition was a dominant mechanism, while for BC350, BC650, and BC750, the major mechanism was a pore-filling.…”
Section: Adsorption Isothermsmentioning
confidence: 99%